2015
DOI: 10.1371/journal.pmed.1001876
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Electronic Reminders to Improve Medication Adherence in Tuberculosis Patients: A Cluster-Randomised Trial

Abstract: BackgroundMobile text messaging and medication monitors (medication monitor boxes) have the potential to improve adherence to tuberculosis (TB) treatment and reduce the need for directly observed treatment (DOT), but to our knowledge they have not been properly evaluated in TB patients. We assessed the effectiveness of text messaging and medication monitors to improve medication adherence in TB patients.Methods and FindingsIn a pragmatic cluster-randomised trial, 36 districts/counties (each with at least 300 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
227
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(264 citation statements)
references
References 16 publications
12
227
1
4
Order By: Relevance
“…None of these EDM studies was powered to assess viral suppression. Additionally, a recent fourarm study using a mix of EDM and SMS for individuals receiving tuberculosis treatment in China found a reduction in incomplete adherence using a combined EDM-SMS approach, but no effect from SMS alone [107].…”
Section: Ict-enhanced Solutionsmentioning
confidence: 99%
“…None of these EDM studies was powered to assess viral suppression. Additionally, a recent fourarm study using a mix of EDM and SMS for individuals receiving tuberculosis treatment in China found a reduction in incomplete adherence using a combined EDM-SMS approach, but no effect from SMS alone [107].…”
Section: Ict-enhanced Solutionsmentioning
confidence: 99%
“…Recently, a limited cluster randomized trial in China found that, while medication monitor reminders led to improved drug compliance for tuberculosis patients, daily two-way SMS reminders did not [18]. Our effectiveness trial gauged the impact of a two-way interactive SMS medication reminder system (Zindagi SMS) on the treatment success of people with drug-sensitive tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent randomized trial of 4,173 tuberculosis patients, text messaging reminders did not significantly improve medication adherence in tuberculosis patients, but smart packaging or smart packaging with reminders did. In the control arm, 29.9% of patients missed at least 20% of doses, while 27.3% and 17.0% and 13.9% missed the same amount of doses in the text reminder, smart packaging, and combined arms, respectively . However, other clinical studies and meta‐analyses have indicated that text message reminders and related digital health apps can increase medication adherence …”
Section: Medication Adherencementioning
confidence: 99%
“…In the control arm, 29.9% of patients missed at least 20% of doses, while 27.3% and 17.0% and 13.9% missed the same amount of doses in the text reminder, smart packaging, and combined arms, respectively. 22 However, other clinical studies and meta-analyses have indicated that text message reminders and related digital health apps can increase medication adherence. [23][24][25][26] While a variety of options are emerging for nonpaper-based adherence technologies, additional work is needed cross-industry to understanding their pros/cons for greater implementation.…”
Section: Medication Adherencementioning
confidence: 99%